2012
DOI: 10.1111/j.1475-6811.2012.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of relationship characteristics that predict new parents' relationship satisfaction

Abstract: Drawing on the relational turbulence model, this study queries whether it is the amount of relational uncertainty and partner interference in a relationship, or the magnitude of an increase in these mechanisms over time, that accounts for decreased relationship satisfaction for new parents. To test these competing hypotheses, a longitudinal study of 78 couples was conducted in which both partners completed surveys about their relationship at 4 time points during the transition to parenthood. Multilevel modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 69 publications
1
46
2
Order By: Relevance
“…Whereas some studies did not find a correlation between relationship duration and satisfaction (Theiss, Estlein, & Weber, 2013), the vast majority of studies concluded that there is a higher probability of being satisfied in earlier phases of partnerships (Nock, 1995;Stafford et al, 2004;Teichner & Farnden-Lyster, 1997;Wiik et al, 2009) and that marital happiness declines over time (Umberson, Williams, Powers, Chen, & Campbell, 2005;VanLaningham, Johnson, this is partly attributable to the effect of growing older, as age shows to be 'more strongly and consistently associated with relationship quality than marital duration'.…”
Section: Couple Characteristics Influencing Relationship Satisfactionmentioning
confidence: 94%
“…Whereas some studies did not find a correlation between relationship duration and satisfaction (Theiss, Estlein, & Weber, 2013), the vast majority of studies concluded that there is a higher probability of being satisfied in earlier phases of partnerships (Nock, 1995;Stafford et al, 2004;Teichner & Farnden-Lyster, 1997;Wiik et al, 2009) and that marital happiness declines over time (Umberson, Williams, Powers, Chen, & Campbell, 2005;VanLaningham, Johnson, this is partly attributable to the effect of growing older, as age shows to be 'more strongly and consistently associated with relationship quality than marital duration'.…”
Section: Couple Characteristics Influencing Relationship Satisfactionmentioning
confidence: 94%
“…On the surface, it would seem that relational uncertainty and interference from partners are not especially prominent upon homecoming following deployment, but we suspect the means may be an artifact of our convenience sampling strategy. Notably, prior tests of the model have documented similar means in studies of both dating relationships (e.g., Knobloch & Theiss, ; Solomon & Knobloch, ; Theiss & Solomon, , ) and long‐term partnerships (Steuber & Solomon, ; Theiss, ) during diverse types of transitions (Solomon et al, ; Steuber & Solomon, ; Theiss et al, ). Although the magnitude of relational uncertainty and interference may be modest in our study, research indicates that even small fluctuations in these variables have negative repercussions within romantic relationships (e.g., Theiss et al, ; Theiss & Solomon, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…The means for relational uncertainty and interference from partners were relatively low, but they are comparable to the means obtained in previous tests of the relational turbulence model. In fact, the means for the mechanisms of relational turbulence are consistently below the midpoint of the scale in studies of both committed romantic relationships (e.g., Steuber & Solomon, ; Theiss et al, ; Theiss & Nagy, 2010) and developing dating relationships (e.g., Knobloch & Theiss, , 2011; Solomon & Theiss, ; Theiss & Knobloch, ; Theiss et al, ; Theiss & Solomon, , ). Taken together, these studies suggest that high levels of relational uncertainty and interference from partners are relatively uncommon among convenience samples.…”
mentioning
confidence: 99%
See 2 more Smart Citations